The Impact of Family Support on Adolescent Engagement During Online Learning: Empirical Study from Makassar City - Nirwana Permatasari; Yassir Arafat; Liliana Sutanto; Farid Firmansyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine the contribution of family support to school engagement among adolescents in Makassar during online learning. One hundred and thirty-four adolescents aged between 14-21 years old were selected as a sample for this research using accidental sampling. The students filled out two instruments: the School Engagement Measure (SEM) and Family Support, adapted and modified). Data were analyzed by using the simple linear regression analysis. This study shows that family support contributes significantly to school engagement among adolescents in Makassar during online learning. The contribution of family support to school engagement is 17.7% (R2= 0.177; Sig = 0.000), while the rest of 82.3% are affected by other variables.